2008
DOI: 10.1007/s00134-007-0977-4
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of phrenic nerve damage after cardiac surgery in children

Abstract: We conclude that the incidence of PND is much higher than currently recognised, and has a very significant effect on post-operative morbidity and mortality. Most children who survive the post-operative period will recover nerve function within 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…ventilation, increased risk of atelectasis and pulmonary infection, prolonged postoperative recovery, increased length of stay in the intensive care unit (ICU), and increased hospitalization costs. 5,6 The diagnosis of DP is suspected clinically in the context of increased work of breathing, persistently elevated hemidiaphragm (on roentgenogram), and failure to separate from positive-pressure ventilation. Diaphragmatic movement can be further evaluated using fluoroscopy and ultrasonography.…”
mentioning
confidence: 99%
“…ventilation, increased risk of atelectasis and pulmonary infection, prolonged postoperative recovery, increased length of stay in the intensive care unit (ICU), and increased hospitalization costs. 5,6 The diagnosis of DP is suspected clinically in the context of increased work of breathing, persistently elevated hemidiaphragm (on roentgenogram), and failure to separate from positive-pressure ventilation. Diaphragmatic movement can be further evaluated using fluoroscopy and ultrasonography.…”
mentioning
confidence: 99%
“…Several other authors have also assessed phrenic nerve function in children after cardiac surgery by using the same technique (Mok et al, 1991). In these prospective studies, the prevalence of DP ranged from 10% to 20% (Mok et al, 1991;Russell et al, 1991Russell et al, , 1993Russell et al, , 2008. However, a study conducted on a small number of children suggested that most prospective studies estimated the prevalence of phrenic nerve palsy on the basis of results from a single electrophysiologic evaluation performed within several days after operation and therefore the prevalence of significant phrenic nerve palsy, which may be transient, was overestimated (Imai et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…13 However, intubation and positive pressure ventilation is not without risk, as it increases the likelihood of infection and lung damage and, if heavy sedation is used, augments muscle atrophy and weakness. 19 Kovacikova et al described two patients in which noninvasive positive pressure ventilation was used to manage respiratory failure resulting from BDP; the first patient was fitted with a nasopharyngeal tube and the second with an anesthaesia oronasal mask, with both patients requiring ventilation pressure control. 5 Although the treatment was noninvasive, complications were reported such as pressure sores over the nasal bridge and cheeks and secondary herpetic and chest infections.…”
Section: Discussionmentioning
confidence: 99%